Preparation and mechanism analysis of an environment‐friendly maize seed coating agent. (13th December 2017) - Zeng, Defang; Fan, Zhao; Tian, Xu; Wang, Wenjin; Zhou, Mingchun; Li, Haochuan
Abstract: BACKGROUND: Traditional seed coating agents often contain toxic ingredients, which contaminate the environment and threaten human health. This paper expounds a method of preparing a novel environment‐friendly seed coating agent for maize and researches its mechanism of action. The natural polysaccharide polymer, which is the main active ingredient of this environment‐friendly seed coating agent, has the characteristics of innocuity and harmlessness, and it can replace the toxic ingredients used in traditional seed coating agents. RESULTS: This environment‐friendly seed coating agent for maize was mainly made up of the natural polysaccharide polymer and other additives. The field trials results showed that the control efficacy of Helminthosporium maydis came to 93.72%, the anti‐feeding rate of cutworms came to 81.29%, and the maize yield was increased by 17.75%. Besides, the LD50 value (half the lethal dose in rats) of this seed coating agent was 10 times higher than that of the traditional seed coating agents. This seed coating agent could improve the activity of plant protective enzymes (peroxidase, catalase and superoxidase dismutase) and increase the chlorophyll content. CONCLUSION: This seed coating agent has four characteristics of disease prevention, desinsectization, increasing yield and safety. Results of mechanism analyses showed that this seed coating agent could enhance disease control effectiveness by improving plant protective enzymes activity and increase maize yield by improving chlorophyll content. © 2017 Society of Chemical Industry